Age and gender influence on HIDRAdisk outcomes in adalimumab‐treated hidradenitis suppurativa patients. (19th September 2019) - Fabbrocini, G.; Marasca, C.; Megna, M.; Peris, K.; ,
Abstract: Background: Hidradenitis suppurativa (HS) is a chronic relapsing inflammatory skin disease characterized by a significant impairment of patients' quality of life (QoL). It has been recently found that clinical severity of HS does not correlate well with QoL. Therefore, it is important to enhance the evaluation of severity considering the disease burden on QoL. Recently, a new graphical tool able to better describe HS burden, the so‐called HIDRAdisk, has been introduced. Objective: To investigate the utility of HIDRAdisk in clinical practice before and after treatment and to analyse whether specific factors such as age and gender may influence the outcomes in patients with moderate‐to‐severe HS. Methods: A single‐centre retrospective study on 24 patients (13F/11M, mean age 38 ± 15 years) with moderate‐to‐severe HS was performed. Clinical data (disease severity and quality of life) were collected at baseline and after 12 weeks of adalimumab. Results: HIDRAdisk showed significantly better improvements in males (69.8 ± 6.2–49.6 ± 10.8) compared to females (80.7 ± 6.0–72.3 ± 6.7), P  <0.001. A significant correlation was found in the total population between HS severity values measured through the modified Sartorius score (mSS) and QoL measured through HIDRAdisk. As regards the relationship between disease outcomes and age, a trend for better HIDRAdisk outcomes in younger patients (<40 years) compared to older ones was observed. Conclusions: HIDRAdisk appears as a complete and informative tool which can easily measure the global burden of HS, guiding treatment choice and evaluating its efficacy.